Derde jaarboedk anarchisme - Adamo, Pietro; Bons, André; Bronsveld, Cees; van den Bruggen, Ferd; Geursten, Ton; Jacobs, Roger; de Raaij, André; Thissen, Siebe; de Winter, Dick (Moerkapelle: De As, 1996)
"Redactie: Marius de Geus, Thom Holterman, Rudolf de Jong, Jaap van der Laan, Wim de Lobel, Bas Moreel, Hans Ramaer ; Verder werkten mee: Pietro Adamo, André Bons, Cees Bronsveld, Ferd van der Bruggen, Ton Geurtsen, Roger Jacobs, André de Raaij, Siebe Thissen, Jan Vis, Dick de Winter. DIGITAAL TE RAADPLEGEN N DE LEESZAAL"